An outlook on current legal status of the employees as the representatives of public authorities - Aristova, Irina V.; Tsybulnyk, Nelli Yu.; Horbonos, Viktoriia V.; Melnyk, Serhii M. (DIXI, 2021)
The purpose of this article is to determine the features of the legal status of employees as representatives of public authorities, taking into account domestic and foreign experience. The main elements of the legal status of employees as representatives of public authorities in Ukraine are considered. It is noted that, as subjects of state power, employees are obliged to have a transparent, clear and unambiguous status in society. Among other things, they must comply in their direct activities with all the necessary norms and principles of domestic and international law, because the professional quality of their work will always be seen as a kind of external face of society. Attention is also focused on the fact that the efficiency of employees is directly related to the level of their self-organization, as well as a number of internal factors. In addition, it emphasizes the importance of civil servants, as well as persons working in public institutions and agencies of proper protection of the rights, freedoms and legitimate interests of men and citizens. Such a requirement for employees follows from the norms and principles of both domestic legislation (including the Basic Law of Ukraine and the Constitution of Ukraine) and international legal acts and declarations signed and ratified by Ukraine. Author’s definitions of “legal status”, “civil servant” as well as “public authority” are offered. Examples of successful experience of some developed, mostly Western, countries in building such conditions for the daily functioning of the state system and society as a whole, which managed to create a proper legal status of civil servants as public authorities, which would meet all important requirements today.
Keywords: legislative consolidation; legal regulation; legal status; legal system; protection of rights and interests; public administration; public authority; civil service